Analysis of the Effect Product Quality, Trustworthiness, Convenience, Perceptions of Usefulness and Price on Purchase Intention During the Covid Pandemic 19 - Gregorius Widiyanto; FX. Pudjo Wibowo (Primanomics : Jurnal Ekonomi & Bisnis, 2021)
This study aims to examine the effect of product quality on buying interest during the Covid 19 pandemic, trust in buying interest during the Covid 19 pandemic, ease of purchase interest during the Covid 19 pandemic, perceived usefulness of purchase interest during the Covid 19 pandemic, and prices on buying interest. The sampling method used was purposive side method, obtained a sample of 140 respondents. Methods of data analysis are using multiple linear regression, T test and F test for data processing using SPSS version 25. The results of this study prove that trust and convenience have a significant effect on buying interest during the Covid 19 pandemic, while product quality, perceived usefulness and price have no effect on purchase intention during the Covid 19 pandemic. While simultaneously have a significant effect on purchase interest in the future